2021
DOI: 10.1016/s2665-9913(21)00140-5
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory trends, hyperinflammation, and clinical outcomes for patients with a systemic rheumatic disease admitted to hospital for COVID-19: a retrospective, comparative cohort study

Abstract: Background COVID-19 can induce a hyperinflammatory state, which might lead to poor clinical outcomes. We aimed to assess whether patients with a systemic rheumatic disease might be at increased risk for hyperinflammation and respiratory failure from COVID-19. Methods We did a retrospective, comparative cohort study of patients aged 18 years or older admitted to hospital with PCR-confirmed COVID-19 at Mass General Brigham (Boston, USA). We identified patients by a search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 27 publications
(43 reference statements)
3
32
0
2
Order By: Relevance
“…Mortality, the primary outcome, was ascertained from the Data Mart but also confirmed by manual EHR review and online searches of obituaries for all cases and comparators to capture deaths that may have occurred outside of the system (15). Secondary outcomes extracted from the Data Mart included hospitalization and mechanical ventilation.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…Mortality, the primary outcome, was ascertained from the Data Mart but also confirmed by manual EHR review and online searches of obituaries for all cases and comparators to capture deaths that may have occurred outside of the system (15). Secondary outcomes extracted from the Data Mart included hospitalization and mechanical ventilation.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…Additionally, it is possible that participants in our study may have had immune system activation as a reaction to SARS-CoV-2 infection that could have contributed to increased activity in addition to DMARD disruption. Indeed, we previously found that participants with SARDs hospitalized for COVID-19 were more prone to hyperinflammation(12). Finally, many participants in the general population report widespread pain and arthralgias after COVID-19, which may have also influenced the high rate of self-reported SARD flare(25-27).…”
Section: Discussionmentioning
confidence: 99%
“…We systematically identified all SARD participants with SARS-CoV-2 confirmed by PCR, nucleocapsid antibody, or antigen testing (from March 1, 2020 to November 3, 2021 for this analysis) at Mass General Brigham (MGB) HealthCare system in the greater Boston, Massachusetts area, as previously described (2,9,(11)(12)(13)(14). This was supplemented by referrals from rheumatologists of participants who were diagnosed outside of the MGB system.…”
Section: Study Populationmentioning
confidence: 99%
“…We utilized the MGB centralized data warehouse to identify patients who were ≥18 years of age and had positive polymerase chain reaction (PCR) testing for SARS-CoV-2 between January 30 th , 2020 and July 30 th , 2021. Patients with SARDs with a positive SARS-CoV-2 test were identified using diagnostic billing codes, as previously described (8)(9)(10)(11)(12).…”
Section: Data Source and Study Populationmentioning
confidence: 99%